Detection of TSC1/TSC2 mosaic variants in patients with cardiac rhabdomyoma and tuberous sclerosis complex by hybrid‐capture next‐generation sequencing. Issue 10 (4th September 2021) - Wang, Siyu; Sun, Hairui; Wang, Jianbin; Gu, Xiaoyan; Han, Lu; Wu, Yuduo; Yan, He; Han, Ling; Zhang, Hongjia; He, Yihua
Abstract: Background: Fetal cardiac rhabdomyoma (CR) is strongly associated with tuberous sclerosis complex (TSC), which is caused by variants in TSC1 and TSC2 . However, in 10%–15% of patients with clinically confirmed TSC, no TSC1 / TSC2 variants are identified by panel sequencing or multiplex ligation‐dependent probe amplification (MLPA). Methods: We analyzed eight fetuses with CR and their families. No TSC1 / TSC2 variants had previously been identified for six of these fetuses, and we suspected the other two families of gonadal mosaicism. We performed next‐generation sequencing (NGS) using CR tissue, umbilical cord tissue, and parental blood. All positive results, involving two paternal semen, were verified by droplet digital polymerase chain reaction (ddPCR). Results: Four fetuses carried low‐level mosaic variants (0.05%–14.89%), and two only exhibited somatic mosaic variants in the CR tissue (15.76% and 37.69%). Two fathers had gonadal mosaicism (9.07% and 4.86%). We identified nine pathogenic variants in eight fetuses, including one fetus with a second‐hit variant. Conclusion: The fetuses assessed in this study carried low‐ level and somatic mosaic variants, and CR tissue from one fetus exhibited a second‐hit variant. Heterozygous gonadal variants can exist in patients with low‐level mosaicism. Combining NGS with ddPCR improves the accuracy of prenatal TSC diagnosis. Abstract : This article was to study the hybrid‐capture next‐generation sequencing (NGS) to detect TSC1 / TSC2 mosaic variants in patients. The fetuses with CR assessed in this study carried low‐level and somatic mosaic variants. Heterozygous gonadal variants can exist in patients with low‐level mosaicism.